2015
DOI: 10.1002/chem.201503551
|View full text |Cite
|
Sign up to set email alerts
|

Large Ferrierite Crystals as Models for Catalyst Deactivation during Skeletal Isomerisation of Oleic Acid: Evidence for Pore Mouth Catalysis

Abstract: Large zeolitec rystals of ferrierite have been used to study the deactivation, at the singlep article level, of the alkyl isomerisation catalysis of oleic acid and elaidic acid by ac ombinationo fv isible micro-spectroscopya nd fluorescence microscopy (both polarised wide-field and confocal modes). The large crystalsd id show the desired activity, albeit only traces of the isomerisation product wereo btained and low conversionsw ere achieved compared to commercial ferrierite powders.T his limited activity is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
3
24
0
1
Order By: Relevance
“…This result is similar to what has been observed in experiments with the same probes in MFI zeolite powder . In the fluorescence maps of each probe molecule, outlines of fluorescence can be observed at the edges of the crystal, which suggests the probes are inserted end‐on into the sinusoidal pore mouths at the surface in a “stopcock” fashion, as previously proposed by Roeffaers et al …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This result is similar to what has been observed in experiments with the same probes in MFI zeolite powder . In the fluorescence maps of each probe molecule, outlines of fluorescence can be observed at the edges of the crystal, which suggests the probes are inserted end‐on into the sinusoidal pore mouths at the surface in a “stopcock” fashion, as previously proposed by Roeffaers et al …”
Section: Resultssupporting
confidence: 89%
“…Although the steric bulk of these probe molecules precludes full entry into the pores, part of the probe molecule may insert itself into the pore mouth of the zeolite end‐on in a “stopcock” fashion. This result suggests that probe molecules can be visualized selectively at the pore mouth of the zeolite crystal, a location of particular interest for catalysis . For example, these probes may be used to detect pore blockage at the surface .…”
Section: Resultsmentioning
confidence: 99%
“…Upon examination of calcined, large crystals of aluminosilicate and borosilicate FER, it was observed that some crystals contained regular dark patches, with representative images in Figure e. In the aluminosilicate material, with a rectangular morphology, the long edge of these dark triangular regions coincides with the longest crystal edge, which contains the opening of the 8‐MRs as depicted in Figure c and was recently reported on by Wiedemann et al . To the best of our knowledge, there are no reports specifically studying the pore orientation with respect to crystal habit in a borosilicate FER material, so it was not possible to make a correlation of the dark region with a certain pore direction.…”
Section: Figuresupporting
confidence: 84%
“…This has led to notable studies including diffusiont hrough a single pore orientation, [17] spatiotemporal diffusion measurements [18][19][20][21][22] and pore-mouth catalysis. [23] The range of crystal habits and aspect ratios are dependento nt he specific synthesis conditions and compositions, and the crystalsa lso have a domed roof with af lat pyramidal morphology as shown in Figure 1c. [16,[24][25][26] Ak ey feature of thesematerials that has enabled many of the aforementioned investigations is that the 8-and 10-MRs run along the long dimensions of the crystal, and the top and bottom crystal faces are impermeable.…”
mentioning
confidence: 99%
“…[164–167] and special issue of ChemPhysChem 2012, 13, 881–1095). Not only they give insight on the orientation of guests, but they also allow to visualize fine details of pore accessibility and connectivity – like the recent demonstration of pore‐blocking during catalytic isomerization in zeolite ferrierite …”
Section: Characterization Techniquesmentioning
confidence: 99%